Neuropsychiatric symptoms and cerebrovascular risk in non-demented elders: cross-sectional study using the mild behavioural impairment checklist (MBI-C) - Stella, Florindo [UNESP]; Pais, Marcos V.; Loureiro, Júlia C.; Radanovic, Marcia; Forlenza, Orestes V. (Wiley, 2022)
Background: Neuropsychiatric symptoms (NPS) may represent early clinical manifestations of evolving brain diseases. Studies underpin the occurrence of NPS in the context of mild cognitive impairment (MCI) and prodromal Alzheimer's disease, where symptoms referred to as ‘mild behavioural impairment’ (MBI) have been shown to predict conversion to dementia and to hasten cognitive/functional decline. However, the association between NPS and cerebrovascular risk factors has been poorly investigated, despite the high prevalence of the latter among individuals with MCI. The aim of the present study was to investigate the association between MBI and cerebrovascular risk in a clinical sample of non-demented elders. Methods: Sixty-five MCI and 15 cognitively unimpaired older adults were cross-sectionally assessed with the Mild Behavioural Impairment Checklist (MBI-C), using the cut-off score > 6.5 to define positive screening. Participants were submitted to the Hachinski Ischaemic Score (HIS) to account for cerebrovascular symptoms, vascular risk, and related comorbidities. Neuroimaging scans (magnetic resonance imaging and/or 18F-fluorodeoxyglucose-positron emission tomography) and apolipoprotein E genotype were obtained. Results: Positive associations were found between total MBI-C scores and increasing number of comorbidities present (0–2 comorbidities), but not with three comorbidities. Two domains of the MBI-C—impulse dyscontrol and social inappropriateness—followed the same trend of the MBI-C total score, with higher scores with the increasing numbers of comorbidities. No significant associations were found between MBI symptoms and HIS or cerebrovascular burden in neuroimaging assessment. Conclusion: We found weak associations between MBI-C total score and the presence of comorbidities with cerebrovascular risk, but not with structural or functional neuroimaging abnormalities or HIS. This finding may represent that the presence of comorbidities adds limited risk to the occurrence of MBI in this sample of non-demented elders.